"Dictionary" human anatomy: features of somatic lexis definition in dictionaries of the Ukrainian, Russian, Polish and English languages - Жуйкова, Маргарита Василівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
Somatic lexis, which includes the partitives – the names of the external parts of the body, has long been the subject of linguistic studies. The proposed research of the lexical meaning of partitives in dictionaries lies at the intersection of lexical semantics, psycholinguistics, and theoretical lexicography. The aim of this article is to analyze four groups of somatisms denoting the head, chest, waist and elbow, and to identify certain trends in their definition, as well as to describe the correlation between definitions and features of conceptualization of somatisms in the minds of native speakers. As research materials are the definitions selected from twelve dictionaries. The main method of research is the definitions analysis, which aims to identify their internal structure and content.The analysis has shown that the definitions of each of the four groups of somatisms do not have identical models of description; all definitions relating to the same part of the body differ in the number of descriptive features and their content. The definitions are dominated by perceptual features obtained by visual observation (shape, structure and localization of the body part); only some definitions have a structural and functional feature (the head contains the brain; the elbow is the place where the arm bends; the waist divides the body into upper and lower parts). The authors of some definitions rely on anatomical concepts that are redundant in dictionaries designed for ordinary speaker. Other illogical aspects of the definition of partitives have been also revealed, in particular the description of the visible part of the body through invisible (brain, bones), reference in definitions to a cultural feature (the waist is defined as the place where the belt is worn). Lexicographic description of the partitives also reveals some difficulties in categorizing of body parts.